Nitroalkene fatty acids modulate bile acid metabolism and lung function in obese asthma - Manni, Michelle L; Heinrich, Victoria A; Buchan, Gregory J; O'Brien, James P; Uvalle, Crystal; Cechova, Veronika; Koudelka, Adolf; Ukani, Dharti; Rawas-Qalaji, Mohamad; Oury, Tim D; Hart, Renee; Ellgass, Madeline; et al. (Scientific reports, 2021)
Bile acid profiles are altered in obese individuals with asthma. Thus, we sought to better understand how obesity-related systemic changes contribute to lung pathophysiology. We also test the therapeutic potential of nitro-oleic acid (NO2-OA), a regulator of metabolic and inflammatory signaling pathways, to mitigate allergen and obesity-induced lung function decline in a murine model of asthma. Bile acids were measured in the plasma of healthy subjects and individuals with asthma and serum and lung tissue of mice with and without allergic airway disease (AAD). Lung function, indices of inflammation and hepatic bile acid enzyme expression were measured in obese mice with house dust mite-induced AAD treated with vehicle or NO2-OA. Serum levels of glycocholic acid and glycoursodeoxycholic acid clinically correlate with body mass index and airway hyperreactivity whereas murine levels of β-muricholic acid and tauro-β-muricholic acid were significantly increased and positively correlated with impaired lung function in obese mice with AAD. NO2-OA reduced murine bile acid levels by modulating hepatic expression of bile acid synthesis enzymes, with a concomitant reduction in small airway resistance and tissue elastance. Bile acids correlate to body mass index and lung function decline and the signaling actions of nitroalkenes can limit AAD by modulating bile acid metabolism, revealing a potential pharmacologic approach to improving the current standard of care.
Keywords: játra; obezita; kyselina glykocholová; usilovný výdechový objem; dusíkaté sloučeniny; Bile Acids and Salts; Drug Evaluation, Preclinical; Asthma; bronchiální astma; Humans; preklinické hodnocení léčiv; lidé středního věku; Forced Expiratory Volume; žlučové kyseliny a soli; Diet, High-Fat; Oleic Acids; kyseliny olejové; Female; antigeny roztočů domácího prachu; mladý dospělý; dospělí; Lung; lidé; zvířata; Thinness; myši; vitální kapacita; plíce; Ursodeoxycholic Acid; myši inbrední C57BL; Antigens, Dermatophagoides; Mice; Vital Capacity; Adult; mastné kyseliny; ženské pohlaví; Liver; respirační alergie; Male; Middle Aged; kyselina ursodeoxycholová; Adolescent; Mice, Inbred C57BL; Glycocholic Acid; Young Adult; dieta s vysokým obsahem tuků; Obesity; Respiratory Hypersensitivity; hubenost; Animals; Anti-Asthmatic Agents; mužské pohlaví; Nitro Compounds; antiastmatika; Fatty Acids; mladiství